Strategi Guru dalam Memamfaatkan Media Pembelajaran Berbasis AI - Lasri Lumbantoruan; Anifah Anifah; Nazla Azzahra; Nataniel Buala Theos Gulo; Ferdi Gunawan Sahputra Pakpahan; Refelita Sari Banjarnahor; Natalia Purba (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study investigates how teachers at SMKN 5 Medan integrate Artificial Intelligence (AI) into learning media. Using a descriptive qualitative method supported by literature review, five teachers participated in this research. The focus includes the types of AI-based media used, the extent of their application, teachers’ comprehension of AI, and the benefits experienced. Results reveal that two teachers still apply conventional methods such as lectures and textbooks, while the other three have started using AI tools like Canva, Gamma, Quizizz, and ClassPoint though only for specific topics. Differences in understanding and implementation levels are evident. Therefore, ongoing training and institutional support are essential to improve the effective use of AI in classroom instruction.